Management of Juvenile Myasthenia Gravis - O'Connell, Karen; Ramdas, Sithara; Palace, Jacqueline (Frontiers in Neurology, 2020)
Juvenile Myasthenia Gravis (JMG) is a rare disorder, defined as myasthenia gravis in children younger than 18 years of age. While clinical phenotypes are similar to adults, there are a number of caveats that influence management: broader differential diagnoses; higher rates of spontaneous remission; and the need to initiate appropriate treatment early, to avoid the long-term physical and psychosocial morbidity. Current practice is taken from treatment guidelines for adult MG or individual experience, with considerable variability seen across centres. We discuss our approach to treating JMG, in a large specialist JMG service, and review currently available evidence and highlight potential areas for future research. First-line treatment of generalised JMG is symptomatic management with pyridostigmine, but early use of immunosuppression, where good control is not achieved is important. Oral prednisolone is used as first-line immunosuppression with appropriate prevention and monitoring of side effects. Second-line therapies including azathioprine and mycophenolate may be considered where there is: no response to steroids, inability to wean to a reasonable minimum effective dose or if side-effects are intolerable. Management of ocular JMG is similar, but requires close involvement of ophthalmology in young children to prevent amblyopia. Muscle-specific tyrosine kinase (MuSK)-JMG show a poorer response to pyridostigmine and anecdotal evidence suggests that rituximab should be considered as second-line immunosuppression. Thymectomy is indicated in any patient with a thymoma, and consideration should be given in acetylcholine receptor (AChR) positive JMG allowing time for spontaneous remission. The benefit is less clear in ocular JMG and is not advised in MuSK-JMG. Children experiencing a myasthenic crisis require urgent hospital admission with access to the intensive care unit. PLEX is preferred over IVIG due to rapid onset of action, but this needs to be balanced with feasibility in very young children. Key questions remain in the management of JMG: when to initiate both first- and second-line treatments, choosing between steroid-sparing agents, and determining the optimal dose and treatment duration. We feel that given the rarity of this disease, the establishment of national registries and collaboration across groups will be needed to address these issues and facilitate future drug trials in JMG.